HEAD TEACHERS ATTITUDE TOWARDS INCLUSIVE EDUCATION THE KEY PREDICTOR OF EFFECTIVE IMPLEMENTATION OF INCLUSIVE EDUCATION IN PUBLIC PRIMARY SCHOOLS OF MURANG’A COUNTY, KENYA - Catherine Nyaguthii Mwarari (International Journal of Educational Best Practices, 2020)
Inclusive education has been accepted as the medium through which learners with disabilities and other special need will access and participate in quality education. Preparedness of implementers of inclusive education in terms of attitudes and knowledge is critical for the effective implementation of inclusive education. Based on the theory of innovation diffusion, this cross-sectional study sought to determine if head teachers and teachers’ knowledge of and attitudes towards inclusive education were predictive of effective implementation of inclusive education. Data were collected from 66 head teachers and 462 teachers from Murang’a County, Kenya, using questionnaires and an observation guide. Multiple regressions was used to analyse the data and results indicated that though head teachers and teachers’ attitudes towards inclusive education and knowledge of inclusive education predicted effective implementation of inclusive education, head teachers’ attitudes had the greatest predictive strength. The implication of the findings is that concerted efforts should be put in place to ensure the acquisition of positive attitudes among implementers of inclusive education specifically head teachers and teachers.